Mystery in the fortune cookie - Warner, Gertrude Chandler, 1890-1979.; Soileau, Hodges (Illinois Albert Whitman & Co., 2003)
Benny finds a handwritten riddle inside his fortune cookie. One cookie leads to another, and the Aldens soon realize they've bitten into another mystery.
7-12.
Keywords: Mystery and detective stories